CERAMIC ELECTRONIC COMPONENT AND METHOD THEREOF - ABE HISAYUKI; TANIGUCHI SUSUMU; TOKUMITSU SHINTARO; YANAGIBASHI RYUGEN; YANAGIDA MIYUKI; KURIMOTO SATOSHI (2012)
PURPOSE: A ceramic electronic component and a manufacturing method thereof are provided to control the thickness deviation of a terminal electrode by forming a terminal electrode using a conductive green sheet. CONSTITUTION: A ceramic small body(1) includes an inner electrode which is buried. A plurality of terminal electrodes(16) is included on the ceramic small body. The terminal electrode includes a first electrode layer(44) which is formed by sintering a conductive green sheet. The terminal electrode also has a second electrode layer(42) which is formed by sintering a conductive paste. The first electrode layer is formed to cover the entire of the second electrode layer.